FRACTAL MODEL AND NUMERICAL SIMULATION OF CONTACT STIFFNESS OF JOINT SURFACE CONSIDERING DOMAIN EXPANSION FACTOR - ZHU ChunXia; CUI Qin; YAN ZhiBiao (Jixie qiangdu)
In order to study the contact stiffness of the bonding surface in more detail from the perspective of fractal theory, on the basis of the M-B fractal model and the Hertz theory, a domain expansion factor is introduced to represent the fractal dimension to establish the normal and tangential contact stiffness fractal models of the bonding surface, respectively. The model comprehensively considers the effects of load, fractal dimension and material parameters on the contact stiffness. At the same time, the change trend of the contact stiffness of the joint surface and each parameter is obtained through numerical simulation.The change trend of normal contact stiffness and normal load is the same, which is opposite to the fractal characteristics and length scale coefficient, but the change trend of the fractal dimension is more complicated, no longer monotonic. The changetrend caused by tangential contact stiffness and the above parameters is similar to that caused by normal contact stiffness.